Optimal simple ratio pigment index for estimating pigment contents of rice - WANG Fu-min; HUANG Jing-feng; LIU Zhan-yu; WANG Xiu-zhen (浙江大学学报. 农业与生命科学版, 2009)
The chlorophyll content and corresponding spectra data were analyzed and new chlorophyll index was constructed to improve the prediction power of chlorophyll content in rice. A rigorous search procedure was used to determine the best narrow band index predictors of rice chlorophyll. In the procedure, all possible simple ratio pigment indices, involving all the two-band combinations between 350 nm and 2500 nm, were derived from the spectra of rice leaf and canopy, and then were regressed against chlorophyll and carotenoid contents using linear models. The pigment index which produced the best fitted model was selected as the optimal index for the corresponding pigment. Finally, the indices presented here were compared with the published simple ratio pigment indices for their performance in estimation of pigment contents. The results show that, at the leaf level, the best suitable pigment indices for estimation of chlorophyll a, chlorophyll b, and total chlorophyll contents, were R737/R709, R568/R1554, and R737/R709, respectively; while at the canopy level, they were R749/R700, R749/R695, R749/R699, and R717/R1776, respectively. The simple ratio pigment indices could give better estimation than most the published pigment indices, especially at leaf level. Through the test, it is found that the performances of these pigment indices in pigment content estimation were equal to or better than those of the published indices. In addition, the bands that composed these new indices were mainly located in red edge region, which was followed by green and short wave infrared region. In conclusion, the pigment indices developed offer technological support for monitoring rice pigment content using remotely sensed data.